Hantavirus cardiopulmonary syndrome: a report of two cases - Marcos Lazaro Moreli; Vivaldo Gomes da Costa; Daiane Pereira da Silva Novaes; Enia Cristina Flor; Juliana Freitas Silva; Keila Rejane Guimarães Vilela; Cácia Régia de Paula (Sociedade Brasileira de Patologia Clínica, 2013)
Infection with hantavirus, from the family Bunyaviridae, causes hantavirus cardiopulmonary syndrome (HCPS) in the Americas. This highly lethal anthropozoonosis afflicts preferentially individuals in rural areas and is transmitted by aerosol of excreta from infected wild rodents. The aim of this study is to report the almost simultaneous occurrence of two cases of HCPS in the municipality of Jataí, state of Goiás, Brazil.